The Impact of Varying the Amounts of Thyme, Rosemary, and Garlic and Their Combination on Local Chickens' Carcass Characteristics and Productive Performance - Asem Ramadan Amar Mohamed,; Abdul hakim Khalefah Alour,; Kholoud Mohammed Alamin Almashat, (African Journal of Advanced Pure and Applied Sciences, 2025)
This work was carried out at the Faculty of Veterinary Medicine and Agriculture, University of Zawia, during the period from March to May 2024, for 6 weeks. The study examined the effect of a mixture of aromatic medicinal plants (thyme, Rosemary, and garlic) at different levels on the productive performance and body weight of local chicks of domestic chickens. The results show that feeding on 100 mg of thyme per kg of feed had a significant increase (P ≥ 0.05) in feed intake during the first and second periods of the study (W1-W3), (W3-W6) was 7679.40 compared to the control group, which gave the lowest value of 7678.00. The average body weight improved significantly for the treatment fed on 100 mg of thyme and rosemary where it recorded a percentage of 252.76 and 282.16, respectively. The weight of the treatment was fed on a mixture of garlic, thyme, and rosemary, where the highest significant difference was recorded at 330 grams. The thyme treatment 100 mg/kg recorded a percentage of 14.10 in the liver and spleen, a percentage of 2.30. The treatment containing a mixture of garlic, thyme, and rosemary affected the heart level, as this treatment recorded the highest significant difference it recorded a percentage of 2.60 grams. The intestinal weights of the various groups did not differ significantly. There was a significant effect on the percentage of cecal weight in groups fed 100 mg thyme, 100 mg rosemary, and 100 mg garlic.